Characterising the anticancer effects of a small molecule with potential to inhibit nuclear import via karyopherin beta1 - Mkwanazi, Nonkululeko (Division of Medical Biochemistry and Structural Biology, 2018)
The Karyopherin superfamily is a group of soluble transport proteins which are involved in nuclear-cytoplasmic trafficking. Studies have shown the involvement of Karyopherin proteins in nuclear pore assembly, nuclear membrane assembly and DNA replication. Since all these cell regulatory functions are critical for normal cell function, dysregulation of Karyopherin proteins may have an impact on cancer cell survival. Previous research in our laboratory and in that of others has shown that Karyopherin Beta 1 (KPNB1) is elevated in and necessary for the survival of cervical cancer cells as inhibiting its expression with siRNAs interfered with the proliferation of cancer cells. KPNB1 has thus been proposed as an anticancer target. In addition to inhibition by siRNA, an in silico screen for small molecules with potential to bind KPNB1 identified a number of compounds that are currently under investigation for their cancer cell killing effects. In this study, we investigated the ability of a novel small molecule 1-benzyl-4[(4-methoxy-1-naphyl) methylamino]-N-methyl pyrrolidine-2-carboxamide (Compound 53) to kill cancer cells and inhibit the activity of KPNB1 cargo proteins. In addition, the in vitro pharmacokinetic properties and in vivo toxicology of Compound 53 (C53) were investigated. Cervical (HeLa and CaSki) and oesophageal (WHCO6 and Kyse30) cancer cell lines were found to be more sensitive to C53 treatment compared to non-cancer cells (FG₀), with EC₅₀ values of ~20 μM for the cancer cell lines and ~30-40 μM for the non-cancer cells. C53 treatment significantly inhibited proliferation in cancer cell lines. The reduction in proliferation in cancer cells was associated with a block in the G1 phase of the cell cycle and a change in the expression of cell cycle related proteins such as CyclinD1 and CDK4. C53 treatment resulted in cell death via apoptosis as observed using Annexin V staining and PARP cleavage. To assess whether C53 interferes with KPNB1 associated nuclear import, we investigated the effect of C53 on the activity of KPNB1 cargo proteins, NFAT and NF-ĸB as well as investigate its effect on KPNB1 localisation. The results show that C53 has no effect on the localisation of KPNB1 but it does however block the nuclear activity of the KPNB1 cargoes, NFAT and NF-ĸB. In order to predict the behaviour of C53 in a living system, in vitro ADME pharmacokinetic studies showed that C53 has moderate solubility, permeability and protein binding however, rapid clearance was shown by liver microsome assay. In vivo repeated dose toxicology studies showed that C53 is tolerable in nude mice. Taken together, the data presented in this study shows that a novel small molecule, C53 has a negative effect on the proliferation of cancer cells, inhibits the nuclear import of KPNB1 cargoes, displays tolerable in vitro ADME pharmacokinetic properties and showed no toxic side effects in vivo. These results suggest that C53 targets KPNB1 and shows potential as an anticancer molecule.